Distributed scheduling for P2P IPTV with low-delay network coding - Sheikh, Anooq Muzaffar; Fiandrotti, Attilio; Magli, Enrico (2013 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting (BMSB), 2013)
This paper presents a distributed push-based packet scheduling algorithm for Peer-to-Peer (P2P) IPTV streaming with Network Coding (NC) over unorganized random network topologies. The benefits of random-push NC for P2P system have been investigated previously, packet scheduling in P2P systems using NC is still largely uninvestigated. The proposed scheduling algorithm aims to opt for a policy that maximizes the number of peers that completely retrieve the media content. We compare the performance of the proposed scheduling algorithm with a typical random scheduler as reference. Our results show increased performance in terms of media quality and bandwidth consumption.